2000
DOI: 10.1164/ajrccm.162.6.9906112
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Volumes For Ventilated Infants Should Be Determined with a Pneumotachometer Placed at the Endotracheal Tube

Abstract: Many ventilators measure expired tidal volume (VT) without compensation either for the compliance of the ventilator circuit or for variations in the circuit setup. We hypothesized that the exhaled VT measured with a conventional ventilator at the expiratory valve would differ significantly from the exhaled VT measured with a pneumotachometer placed at the endotracheal tube. To investigate this we studied 98 infants and children requiring conventional ventilation. We used linear regression analysis to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 11 publications
2
53
0
Order By: Relevance
“…The accuracy and precision of delivered V T with this method remains controversial in smaller infants, especially if the lung compliance is less than that of the ventilator circuit. 45,46 It must be noted that all measurements, irrespective of source, are affected by ETT leaks, humidification, ventilator circuit compliance, and airway secretions. Some centers remove patients from volume-targeted ventilation if the ETT leak is Ͼ 30% or re-intubate with a larger ETT to eliminate the leak, so a volume-targeted mode can be used.…”
Section: Pressure Control Ventilation Versus Volume-targeted Ventilationmentioning
confidence: 99%
“…The accuracy and precision of delivered V T with this method remains controversial in smaller infants, especially if the lung compliance is less than that of the ventilator circuit. 45,46 It must be noted that all measurements, irrespective of source, are affected by ETT leaks, humidification, ventilator circuit compliance, and airway secretions. Some centers remove patients from volume-targeted ventilation if the ETT leak is Ͼ 30% or re-intubate with a larger ETT to eliminate the leak, so a volume-targeted mode can be used.…”
Section: Pressure Control Ventilation Versus Volume-targeted Ventilationmentioning
confidence: 99%
“…However, for infants and smaller children, a substantial proportion of the delivered V T may be lost due to circuit distensibility. Cannon et al 39 found that for neonatal circuits the expiratory V T measured at the endotracheal tube was on average only 56% of that measured at the expiratory valve. Somewhat improved correlation was found with pediatric circuits: the average measured V T at the endotracheal tube was 73% of that measured at the ventilator.…”
Section: Tidal Volumementioning
confidence: 99%
“…A key element for all systems is the ability to measure the volume of gas that actually reaches the patient by measuring it not at the machine but at the patient wye. 13 Volume-targeted breaths classically produce a square flow waveform, in which inspiratory flow is held constant until inspiration ends. This results in a steady ramping of pressure and volume, such that peak volume delivery and pressure occur at the end of inspiration.…”
Section: Pressure-targeted Modalitiesmentioning
confidence: 99%